2003
DOI: 10.7227/ijmee.31.1.1
|View full text |Cite
|
Sign up to set email alerts
|

An Engineer's Approach to a General Algorithm for Finding the Sum of Powers of Natural Numbers

Abstract: Convenient formulae for finding the sums of kth power of the first n natural numbers may be useful in some engineering applications. The formulae for k = 1, 2, and 3, are commonly found in the literature. In this paper, an attempt is made to develop a general algorithm for finding the sum for any positive integer value of k. The development of the algorithm is entirely an engineering approach, based purely on a simple geometric interpretation and does not involve any deep mathematics. This algorithm may be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It has been shown that the sum of the kth power of the first n natural numbers may be expressed as a polynomial of order (k + 1) without a constant term [1]. Hence, it may be expressed as: (1) where a k,j is the coefficient of n j of the polynomial.…”
Section: Observations Of the Formulaementioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that the sum of the kth power of the first n natural numbers may be expressed as a polynomial of order (k + 1) without a constant term [1]. Hence, it may be expressed as: (1) where a k,j is the coefficient of n j of the polynomial.…”
Section: Observations Of the Formulaementioning
confidence: 99%
“…Hence, it may be expressed as: (1) where a k,j is the coefficient of n j of the polynomial. The formulae presented in reference [1], together with some more formulae, may be expressed in polynomial form and the values of various coefficients may be tabulated as in Table 1. It may be noted that k = 0 is an obvious result which is included only to complete the triangular form of Table 1.…”
Section: Observations Of the Formulaementioning
confidence: 99%
See 3 more Smart Citations